Structure and quality of pasta enriched with functional ingredients - Bustos Shmidt, Mariela Cecilia (2015)
Dry pasta is a traditional cereal-based food product that is becoming increasingly popular worldwide because of its convenience, palatability, and nutritional quality. The low cost and the long shelf life of pasta, as well as the fact that it is consumed by people of all ages and from all walks of life, make this a suitable product to be enriched with functional ingredients of various types and origins. In this article we review current knowledge on the fate of those functional components that have been more widely studied, how they may interact during processing and what impact they may have on quality attributes. In particular, the specific interactions between key components (starch and proteins) during lamination, extrusion and drying are reviewed. As far as we know, few review articles consider the addition of different types of functional ingredients of various physicochemical properties to pasta formulation or how such addition affects pasta quality. This journal is